2022
DOI: 10.7759/cureus.31313
|View full text |Cite
|
Sign up to set email alerts
|

Role of Probiotics in Human Health

Abstract: Certain bacteria, known as probiotics, have had a vastly beneficial effect on people's health; considering their benefits they have been mixed with a wide variety of foods for several decades now. The ability of probiotics to modify the immunological response of the host, antagonize pathogenic microbes, or compete for adhesion sites with pathogenic microorganisms is related to the action of probiotics against microorganisms. Infections of the digestive tract, irritable bowel, lactose intolerance, allergies, in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
26
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 38 publications
(26 citation statements)
references
References 48 publications
0
26
0
Order By: Relevance
“…Irritable bowel syndrome (IBS), celiac disease, and other intestinal illnesses have been linked to a deficiency of beneficial bacteria in the gut. Beneficial probiotics in the gastrointestinal tract inhibit pathogenic microbes by competing for space and resources, thereby preventing them from infiltrating and proliferating (Bodke & Jogdand, 2022). Probiotics can beneficially modulate the human immune system in conjunction with the host's original microbiota (Bodke & Jogdand, 2022).…”
Section: Probiotics and Health Effectsmentioning
confidence: 99%
See 1 more Smart Citation
“…Irritable bowel syndrome (IBS), celiac disease, and other intestinal illnesses have been linked to a deficiency of beneficial bacteria in the gut. Beneficial probiotics in the gastrointestinal tract inhibit pathogenic microbes by competing for space and resources, thereby preventing them from infiltrating and proliferating (Bodke & Jogdand, 2022). Probiotics can beneficially modulate the human immune system in conjunction with the host's original microbiota (Bodke & Jogdand, 2022).…”
Section: Probiotics and Health Effectsmentioning
confidence: 99%
“…Beneficial probiotics in the gastrointestinal tract inhibit pathogenic microbes by competing for space and resources, thereby preventing them from infiltrating and proliferating (Bodke & Jogdand, 2022). Probiotics can beneficially modulate the human immune system in conjunction with the host's original microbiota (Bodke & Jogdand, 2022). Upon ingesting probiotics, they first adhere to the recognition receptors on the surface of the intestinal epithelial cells, thus triggering a cascade of immunological responses (Raheem et al, 2021).…”
Section: Probiotics and Health Effectsmentioning
confidence: 99%
“…10 They may be used to treat inflammatory diseases, urogenital infections, and a variety of gastrointestinal illnesses. 11 They have positive immunomodulatory effects, including intraepithelial modulation and activation, as well as cytokine synthesis triggered by macrophage and natural killer cell activation. 12,13 Due to the fact that probiotic bacteria perform several activities, they are currently being employed in a wide variety of scientific fields to combat a variety of ailments.…”
Section: Probiotics As Pro-healersmentioning
confidence: 99%
“…Recently, extensive studies have been conducted on the effect of fermented food products on human health, including probiotics (PBT) and fermented dairy products, as either prophylactic or therapeutic nutraceuticals [ 1 ]. PBTs are considered one of the food supplements that are produced using non-pathogenic microorganisms that improve and restore gut commensal microbiomes (GMs) [ 2 ]. Reports evidenced that PBTs could potentially improve a variety of gastrointestinal disorders and improve health [ 3 ].…”
Section: Introductionmentioning
confidence: 99%
“…Several studies have shown the ameliorative properties of PBTs as food supplements via the regulation of imbalanced GM [ 7 ]. Moreover, PBTs have demonstrated alleviation of immuno-inflammatory issues associated with multiple health conditions, including diabetes, inflammatory bowel syndrome (IBS), neuro-inflammatory illnesses and MS [ 2 , 8 , 9 , 10 ]. Currently, live PBT cultures are part of fermented dairy products.…”
Section: Introductionmentioning
confidence: 99%